PENGARUH BRAND AWARENESS, BRAND TRUST DAN ECONOMIC BENEFIT TERHADAP KEPUTUSAN PEMBELIAN POLIS ASURANSI JIWA UNIT LINK PT. AJ SEQUISLIFE DI SOLO (Studi Kasus Pada Nasabah yang Sudah Pernah Membeli Polis di Sequislife) - Priastuti, Wahyu (KELOLA, 2018)
This study aims to determine the effect of brand awareness, brand trust, and economic benefits to the life insurance unit purchase decision unit link PT.AJ Sequislife in Solo. sample in this research is people who have bought life insurance policy PT.AJ Sequislife in Solo especially unitlink product. The respondents used in this research are 100 people. Analytical techniques in this study consisted of testing instrument validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test and R2 test. The results of the analysis show that brand awareness, brand trust, and economic benefit together have a significant influence simultaneously to the life insurance unit purchase decision of PT.AJ Sequislife unit link in Solo. The result of test of R2 (coefficient of determination) is known that brand awareness, brand trust, and economic benefit is able to explain 60,9% to the variable of life insurance unit decision of PT.AJ Sequislife unit link in Solo, while the rest equal to 39,1% other than variable brand awareness, brand trust, and economic benefit. Keywords: brand awareness, brand trust, and economic benefit, purchase decision.